Gestión contable y financiera para los microemprendimientos en el sector ferretero - Borbor Jiménez, Rolando Emmanuel (2023)
The present work called Accounting and Financial Management for Micro Enterprises in the Hardware Sector, reports on the accounting problems presented by the owners within their businesses and their influence on finances, the data analyzed by previous studies and the conceptual framework denote that this problem has transcended over time and that the controls and support provided by accounting and finance have provided support to companies that maintain adequate management. In the application of a mixed type research approach, the ex post fact cross-sectional type research of the years 2018 and 2019 was selected, and through the descriptive type research it allowed the application of the inductive and analytical methods that enabled a qualitatively, quantitatively and sufficiently to address the analysis objectives..............